(untitled) (Per Musi, 2014)
In this article, we articulate the group’s musical production within the context of MPB (Música Popular Brasileira) in the early 1970s, marked mainly by the country’s dictatorship in its most repressive period coupled with the consolidation of the country’s music industry. Regarding the first two albums, which share the same title, we analyse the lyrics of the songs, which reveal political positions and cultural values of the 1970s generation, which suffered the dictatorial repression while receiving delayed information from foreign counterculture and the hippie movement.